Feeding and nutrient requirements of Sultan fish, Leptobarbus hoevenii: A review - Au, Hsein Loong; Lim, Leong Seng; Thumronk Amornsakun; Sharifah Rahmah; Hon, Jung Liew; Poramat Musikarun; Pornpanom Promkaew; Wen Jye Mok; Gunzo Kawamura; Annita Yong Seok Kian; Rossita Shapawi; Saleem Mustafa (2020)
Sultan fish (Leptobarbus hoevenii) is a commercially important freshwater fish with high potential for aquaculture production in the Southeast Asian countries, including Malaysia. Many studies have been focused on its nutrition and trophic biology but the feeding practices in the farming have not yet been reviewed. This paper reviews on nutritional management of L. hoevenii broodstock, larvae and juveniles in culture systems. In general, there are feeding guidelines developed for the L. hoevenii farming but they are not fully supported with the scientific studies. Knowledge on the larval developmental biology is lacking to fully understand the feeding ecology of this fish. In addition, there is a paucity of data on requirements of various major nutrients in L. hoevenii at different life stages. Further studies on these topics are essentially required to improve the feeding practices in the farming of L. hoevenii.